How genomics can help biodiversity conservation - Theissinger, Kathrin; Fernandes, Carlos; Formenti, Giulio; Bista, Iliana; Bleidorn, Christoph; Bombarely, Aureliano; Crottini, Angelica; Gallo, Guido R.; Godoy, José A.; Jentoft, Sissel; Mouton, Alice; Oomen, Rebekah A.; et al. (Trends in genetics, 2023)
Genomics provides effective tools to characterize biodiversity, but the full implementation of genomic techniques in practical conservation is still limited. We review some of the main approaches in biodiversity genomics available to conservationists and genomicists.High-quality, long-read sequencing and bioinformatic technologies facilitate genome sequencing and assembly for any species. We summarize how reference genomes, in conjunction with population genomic data, can contribute to biodiversity monitoring, conservation, and restoration efforts.Over the past decade, many initiatives to generate reference genomes spanning the tree of life have emerged worldwide. We call for increased integration of reference genomes and population genomics data into interdisciplinary conservation efforts to fully unlock the potential of genomics in safeguarding global biodiversity. The availability of public genomic resources can greatly assist biodiversity assessment, conservation, and restoration efforts by providing evidence for scientifically informed management decisions. Here we survey the main approaches and applications in biodiversity and conservation genomics, considering practical factors, such as cost, time, prerequisite skills, and current shortcomings of applications. Most approaches perform best in combination with reference genomes from the target species or closely related species. We review case studies to illustrate how reference genomes can facilitate biodiversity research and conservation across the tree of life. We conclude that the time is ripe to view reference genomes as fundamental resources and to integrate their use as a best practice in conservation genomics.